(3fXQjI GdJfXje hGdJSjjQ (B: s (3ehLgI dWdHI (B: (3GdSfI GdKGfjI LPY eTJQc (B/ s - (3bUQj, aQjOIs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2022)
(3eaghe GdYedjI GdJfXjejI , eaghe GdYedjI GdJSjjQjI , eaghe GdefXeI , GdeOGNd GdfXQjI GdeaSQI ddJfXje h GdJSjjQ , GdgjGcd GdJfXjejI ,fXQI eYGUQI Gdi GdgjGcd GdJfXjejI , GdbjGOI GdGOGQjI , egGQGJ h eHGOF GdbjGOI GdGOGQjI , GfeGW GdbjGOI GdGOGQjI , GdfXQjGJ GdeaSQI ddbjGOI GdGOGQjI , GdeYjbGJ GdJj JhGLggG GdbjGOI GdGOGQjI (B. s
(3GdeQGLY U(B.106s
Keywords: (3GOGQI GdGYeGds; (3GdJfXjes